PELANGGARAN MAKSIM KERJA SAMA DALAM FILM MIRACLE IN CELL NO. 7 VERSI INDONESIA KARYA HANUNG BRAMANTYO - Andi Tenri Sua; Andi Paradilla Astifa; Suhardiman Suhardiman; Antika Utami Putri; Elihami Elihami (Universitas Negeri Makassar, 2026)
This study aims to describe the forms of violations of cooperative maxims in the Indonesian version of the film Miracle in Cell No. 7 by Hanung Bramantyo. This research employs a qualitative approach with a descriptive method. The data source for this study is the Indonesian version of the film Miracle in Cell No. 7, whereas the research data are utterances that contain violations of conversational maxims based on Grice's cooperative principle theory. Data were collected using observation and note-taking techniques, and data analysis employed reduction, classification, and interpretation techniques. The results of the study indicate violations of four maxims: the maxims of quantity, quality, relevance, and manner, with a dominant tendency toward violations of the maxims of relevance and quality. These violations serve to build conflict, strengthen character development, and create dramatic effects within the plot.